Very early and severe presentation of Triple A syndrome – case report and review of the literature - Cehic, Maja; Mitrovic, Katarina; Vukovic, Rade; Milenkovic, Tatjana; Kovacevic, Gordana; Todorovic, Sladjana; Panic Zaric, Sanja; Cvetkovic, Dimitrije; Paripovic, Aleksandra; Huebner, Angela; Koehler, Katrin; Quitter, Friederike (Frontiers in Endocrinology, 2024)
Triple A syndrome (TAS), also known as Allgrove syndrome (OMIM#231550), is a rare, autosomal recessive disorder characterized by the triad of alacrima, achalasia, and adrenal insufficiency. Additional neurological features may be present in two-thirds of patients, involving central, peripheral, and autonomic nervous system manifestations. TAS is caused by genetic alterations in the AAAS gene on chromosome 12q13, which encodes the nuclear pore complex protein termed ALADIN (ALacrima, Achalasia, aDrenal Insufficiency, and Neurologic disorder).ALADIN plays a crucial role in nucleocytoplasmic transport of specific proteins, including the transport of DNA repair proteins. TAS exhibits significant phenotypic variability in terms of symptom onset, frequency, and severity, often presenting with a progressive clinical course indicative of an underlying degenerative process.In this study, we report the case of an infant with exceptionally early and severe manifestations of triple A syndrome, with a review of the literature. Our patient exhibited the complete classical triad of TAS at six months of age, being amongst the youngest reported cases of the syndrome.The clinical course was complicated by severe involvement of the autonomic nervous system, neurogenic bladder, and recurrent urinary tract infections. Subsequently, the patient developed acute pancreatitis, leading to multiorgan dysfunction and a fatal outcome at 25 months of age. This case underscores the potential for atypical disease presentations and the need for clinical awareness in diagnosing and managing patients with TAS.